A liminal lens on integrating refugees into the workplace: Conceptualising a theoretical model. (5th February 2021) - Loon, Mark; Vitale, Agata
Abstract: The integration of refugees into workplaces in their destination country remains a global concern. We meet the challenge of this problem by conceptualising a theoretical model using a liminal lens; more specifically, through the three thematic lenses of liminality as process, liminality as position and liminality as place. By addressing the research question; 'how does a liminal lens provide new insights into refugees' integration into the workplace?' we make three contributions to extant literature. First, we offer a dynamic perspective of refugees' integration into the workplace. Second, we provide a synthesis that brings together key factors at the micro, meso and macro levels that are germane to refugees' assimilation into the workplace. Finally, we contribute to human resource (HR) literature by showing a more nuanced view of the role of human resource management, specifically how an ambidextrous HR architecture can help firms explore refugees as a talent pool, while exploiting existing talents.